(3Sdhc GdeGdc aj JOHjQ GdeeeGdcs - (3GHf CHj GdQHjY, CMeO Hf eMeO Hf CHj GdQHjY, J (B272s ((3eMeO Ydj GdNQGSGfjs)
(3ChdgG (B:s
(3HYO GdHSedI ; hGdMeO ddg GdPj Ndb GdEfSGf aj CMSjf Jbhje hHYO aEf GdPj HYK Gdeedhc Ydi JCdja gPG GdcJGH CeQGf CeG GdChd aEfg hba Ydi cJGH eTLQ aj MaX GdHOf hGdKGfj Cf HYV ef ChGeQg eWGYI eLGHIs
(3BNQgG (B:s
(3aj BNQg LOhd Hg hUGjG CQSWhs
(3aj BNQg (B: (3JbGQjX h ahGFO ddcJGH deUeeg eMeO GdSedhWjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1/205s
(3eYLe GdeDdajf (B1/246s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdadSaI hGdefWbs